Specific Absorption Rate and Maximum Permissible Input Power of Planar Inverted-F Antennas - Nurul Inshirah Mohd Razali; Norhudah Seman; Nor Aishah Muhammad (Results in Engineering)
The electromagnetic wave radiation toward human heads has gained attention due to a large number of mobile phone usage, especially concerning the planar inverted-F antenna (PIFA), which is commonly used in these devices. Therefore, it is essential to investigate the radiation from mobile phones utilizing PIFA across mobile operating frequencies. Hence, this article investigates the specific absorption rate (SAR) of a rectangular-shaped planar inverted-F antenna (PIFA) at frequencies ranging from 0.835 GHz to 2.6 GHz. These PIFAs are implemented as the radiation source to investigate the SAR at the concerned mobile operating frequencies through simulation and measurement focusing on various input power, antenna gain, and antenna maximum permissible input power for SAR compliance. The PIFA is placed at a distance of 10 mm from the human head phantom in the investigation. The results show that operating frequency is not a primary factor influencing the level of SAR on PIFA, as highlighted in the previous works. However, it is noted that the SAR of PIFA is proportional to the input power and volume of mass tissue. Higher input power leads to a higher SAR value as more radiated energy is absorbed by the human head, while the lower mass of tissue results in the higher SAR due to the higher concentration of power absorption for the smaller tissue mass. Furthermore, a key finding reveals that the SAR of PIFA follows the same trend as its gain. The increment of gain enhances the radiation efficiency of the antenna, which subsequently increases the absorption level within the human head, leading to a higher SAR. In order to comply with the standard limit, the PIFA's maximum permissible input power also follows the trend of antenna gain, with 1 g of mass tissue needing a lower maximum permissible input power compared to 10 g of mass tissue.